Transcriptomic Effects of the Cell Cycle Regulator LGO in Arabidopsis Sepals - Schwarz, Erich M.; Roeder, Adrienne H. K. (Frontiers in Plant Science, 2016)
Endoreduplication is a specialized cell cycle in which DNA replication occurs, but mitosis is skipped creating enlarged polyploid cells. Endoreduplication is associated with the differentiation of many specialized cell types. In the Arabidopsis thaliana sepal epidermis endoreduplicated giant cells form interspersed between smaller cells. Both the transcription factor Arabidopsis thaliana MERISTEM LAYER1 (ATML1) and the plant-specific cyclin dependent kinase inhibitor LOSS OF GIANT CELLS FROM ORGANS (LGO)/SIAMESE RELATED1 (SMR1) are required for the formation of giant cells. Overexpression of LGO is sufficient to produce sepals covered in highly endoreduplicated giant cells. Here we ask whether overexpression of LGO changes the transcriptome of these sepals. We show that overexpression of LGO in the epidermis (LGOoe) drives giant cell formation even in atml1 mutant sepals. Using RNA-seq we show that LGOoe has significant effects on the sepal transcriptome that are primarily ATML1-independent changes of gene activity. Genes activated by LGOoe, directly or indirectly, predominantly encode proteins involved in defense responses, including responses to wounding, insects (a predator of Arabidopsis), and fungus. They also encode components of the glucosinolate biosynthesis pathway, a key biochemical pathway in defense against herbivores. LGOoe-activated genes include previously known marker genes of systemic acquired resistance such as PR1 through PR5. The defensive functions promoted by LGOoe in sepals overlap with functions recently shown to be transcriptionally activated by hyperimmune cpr5 mutants in a LGO-dependent manner. Our findings show that the cell cycle regulator LGO can directly or indirectly drive specific states of gene expression; in particular, they are consistent with recent findings showing LGO to be necessary for transcriptional activation of many defense genes in Arabidopsis.